Neural Signatures of Gender Differences in Interpersonal Trust - Wu, Yan; Hall, Alisha S. M.; Siehl, Sebastian; Grafman, Jordan; Krueger, Frank (Frontiers in Human Neuroscience, 2020)
Trust plays a critical role in nearly every aspect of social life. Parental investment theory and social role theory predict that women trust less than men due to a higher sensitivity to risk and betrayal, while men trust more than women to maximize resources and to signal their willingness to lose something. However, the underlying neuropsychological underpinnings for this gender difference are still obscure. In this study, we used functional magnetic resonance imaging (fMRI) to investigate the neural signatures of gender differences in trust by simultaneously scanning 11 male and 11 female same-gender, fixed dyads who played a multi-round binary trust game with varying levels of payoff (low/moderate/high) as an indicator of social risk. Our results showed that men trusted more than women and payoff level moderated the effect of gender on trust. While men trusted the same at all payoff levels, women trusted less with higher payoff levels. This pattern was supported by our neuroimaging finding: men showed a higher activation in the left inferior frontal gyrus (ventrolateral prefrontal cortex) and right precuneus than women, indicating that men exert more effort to inhibit the information of payoff levels and to use self-referencing to infer the strategies of partners with the goal of maximizing profit. Furthermore, men showed equivalent activation in the subgenual anterior cingulate cortex across payoff levels, whereas women showed a decreased activation with increasing payoff level—indicating decreased group bonding with higher risk in women. In conclusion, our results imply that women are more sensitive to social risk while trusting, which has implications for financial interactions, interpersonal relationships, and social involvement.